(untitled) (Bangladesh Journal of Neurosurgery, 2020)
Introduction: To review the surgical approaches, techniques, outcomes and recurrence rates in a series of 11 olfactory groove meningioma (OGM) patients operated from January 2010 to April 2019. Methods: Eleven patients underwent craniotomy and micro-neurosurgical removal of olfactory groove meningioma. Tumor diameter varied from 5 to 8.5 cm among 11 cases, 2 cases underwent Transglabellar/ Subcranial approach, 3 cases by bifrontal approach, 1 case unifrontal approach, 2 extended endonasal and 3 cases fronto-lateral approach. Result: Total removal was possible in all cases except 2 cases. Histopathology revealed typical meningioma (WHO grade 1). There was 1 operative mortality and no permanent focal neurological deficit except anosmia. 3 patients developed CSF leak and two cases meningitis which were resolved by lumber drain and antibiotic therapy. Conclusion: Extended endonasal approach or transglabellar/ subcranial approach were sufficient for gross total removal of OGM which is associated with bony hyperostosis, paranasal extension and optic canal. Bang. J Neurosurgery 2020; 10(1): 9-19